2019
DOI: 10.17576/jkmjc-2019-3502-21
|View full text |Cite
|
Sign up to set email alerts
|

Improving Psychological Well-being Among Undergraduates: How Creativity in Learning Can Contribute?

Abstract: Psychological well-being (PWB) is considered an important variable since it correlates with many other important variables, particularly in mental health. Nevertheless, studies on PWB among university undergraduates are limited. This in turn, limits our ability to provide interventions to increase their PWB. As such, the purpose of this study is to assess levels of psychological well-being among undergraduates and to suggest how creativity can contribute to the enhancement of PWB. We also assessed PWB of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This finding corroborates the study of Fayolle and Gailly (2015) which states that students with higher levels of creativity and innovative thinking tend to have stronger zeal to be entrepreneurial in nature. Furthermore, this result aligns with the study by Khairani et al (2019), that undergraduate creative students tend to think outside the box and come up with innovative solutions, which is essential for identifying and pursuing viable business opportunities. This suggests that creativity is crucial in generating innovative business ideas and identifying entrepreneurial opportunities.…”
Section: Discussion Of Findingssupporting
confidence: 85%
See 1 more Smart Citation
“…This finding corroborates the study of Fayolle and Gailly (2015) which states that students with higher levels of creativity and innovative thinking tend to have stronger zeal to be entrepreneurial in nature. Furthermore, this result aligns with the study by Khairani et al (2019), that undergraduate creative students tend to think outside the box and come up with innovative solutions, which is essential for identifying and pursuing viable business opportunities. This suggests that creativity is crucial in generating innovative business ideas and identifying entrepreneurial opportunities.…”
Section: Discussion Of Findingssupporting
confidence: 85%
“…It has been recognized as one of the important skills that should be developed among students from higher education in the 21st century. Khairani et al (2019) stated that creativity can contribute to enhancing undergraduates' psychological well-being. Students with strong creative skills can generate new and innovative business ideas, products or services (Kumar and Shukla 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It involves dimensions such as autonomy, personal growth, self-acceptance, positive relations with others, purpose in life, and environmental mastery (18). Sustained psychological well-being does not imply constant happiness but includes the ability to navigate and manage painful emotions, an essential component of long-term well-being (19). The multifaceted nature of bereavement, encompassing psychological theories and coping strategies, underscores the complexity of the grief process and the need for a personalized approach to dealing with loss.…”
Section: Introductionmentioning
confidence: 99%
“…Udhayakumar & Illango (2018) have focused on the mental health and physical health of the students where they found that the students who are facing anxiety, depression and other psychological dysfunctions in their life, their physical health is also getting affected by that. Nevertheless, Khairani et al, (2019) have focused on how psychological dysfunction can be reduced and the study finds that if the students focus more on creative work, it can improve their personal growth and psychological well-being as well. Covid-19 situation has given a chance to rethink all these aspects for students' psychological well-being.…”
Section: Introductionmentioning
confidence: 99%